Performance of re-used pacemakers and implantable cardioverter defibrillators compared with new devices at Groote Schuur Hospital, Cape Town, South Africa - Jama, Zimasa Vuyo (Department of Medicine, 2016)
Objectives: Little is known about the performance of re - used pacemakers and implantable cardioverter defibrillators (ICDs) in Africa. We sought to compare the risk of infection and the rate of malfunction of re - used pacemakers and ICDs with new devices at Groote Schuur Hospital in Cape Town, South Africa. Methods: This was a retrospective case comparison study of performance of re - used pacemakers and ICDs in comparison with new devices at Groote Schuur hospital over a 10 year period. The outcomes were incidence of device infection, device malfunction, early battery depletion, and device removal due to infection, malfunction, or early battery depletion. Results: Data for 126 devices implanted in 126 patients between 2003 and 2013 were analysed, of which 102 (81%) were pacemakers (51 re - used and 51 new) and 24 (19%) were ICDs (12 re - used and 12 new). There was no device infection, malfunction, early battery depletion or device removal in either the re - used or new pacemaker groups ov er the median follow up of 15.1 months (interquartile range (IQR), 1.3 - 36.24 months) for re - used pacemakers and 55.8 months (IQR, 20.3 - 77.8 months) for new pacemakers. In the ICD group, no device infection occurred over a median follow up of 35.9 months (I QR, 17.0 - 70.9 months) for re - used ICDs and 45.7 months (IQR, 37.6 - 53.7 months) for new ICDs. One device delivered inappropriate shocks which resolved without intervention and no harm to the patient, this re - used ICD subsequently needed generator replacement 14 months later. In both, the pacemaker and ICD groups, there were no procedure non related infections documented for the respective follow up periods. Conclusion: No significant differences were found in performance between re - used and new pacemakers and ICDs with respect to infection rates, device malfunction, and battery life and device removal for complications. Pacemaker and ICD reusee is feasible and safe and is a viable option for patients with bradyarrhythmias and tachyarrthythmias.